Kontroversi Sosial Caleg Perempuan PKS (Komunikasi Politik, Dogma Agama & Afirmasi) - Fauzi, Agus Machfud; Novinayah, Fadilah Salsa; Darmawan, Oktavia Ayu; Rivaldi, Rivaldi (MEDIAKOM : Jurnal Ilmu Komunikasi, 2019)
This study aims to explain the implementation of government policies related to a 30% quota for women in the East Java PKS DPW, in addition to knowing its implementation. The social controversy responding to the PKS policy in presenting female legislative candidates aims to show to the public that there is a conflict between government policy and Islamic dogma which is the principle in the PKS. This study used qualitative research methods. The results showed that the implementation of government policies related to the 30% quota for women in the PKS East Java DPW had exceeded those specified, which was at 46%, whereas according to their interpretation that the prevailing religious dogma had no conflict between prevailing teachings with the government's policy of 30% of women's quota, all of them have their share in life. Al-Quran Surah An-Nisa verse 34 and Surah Al-Ahzab verse 33 textually prohibit women from becoming leaders, this is a source of religious dogma. Social controversy about women becoming leaders is eliminated when they have competence and capacity because the existence of leaders here is not in the context of congregational prayer but rather in carrying out state and national work programs.